On restrictions and generalizations on comma-free codes - Magpantay, Daryl Mendoza (Animo Repository, 2012)
This paper is an exposition of the article entitled \Restrictions and Generalizations on Comma-Free Codes by Alexander L. Churchill [7]. The highlight of this paper is the discussion of series of bounds of two new classes, self-re ective and self swappable comma-free codes. Comma-free dictionary (D) is a set of k-letter code words satisfying the condition that whenever (a1a2 ak) and (b1b2 bk) are in D, the overlays or overlaps (a1a1 akb1 : : : bi1) where 2 i k are not in D. Self-re ective comma-free dictionary Dr is a subset of D satisfying the condition that for all words ! 2 Dr, (!) 2 Dr where (a1a2 ak) = (akak1 a2a1). By self-swappable comma-free dictionary Ds, it is xed under the permutation f(!) = (a1a2)(a3a4) (an1an) where all all are members of an n-letter alphabet where n is even.